Passionate nutrition : a guide to using food as medicine from a nutritionist who healed herself from the inside out - Adler, Jennifer (Sasquatch Books, 2014)
"This power foods healthy living guidebook will inspire readers will eat well, lose weight, and embrace food as medicine. "Food as medicine" is a powerfully healing way to eat and was embraced by nutritionist Jennifer Adler as she recovered from a malnourished childhood and adolescence. Part power-foods cookbook, part handbook for healthy living and eating, and part memoir, Passionate Nutrition provides digestible information, tips, and techniques for how to find your way to optimal health. She focuses on abundant eating (as opposed to restrictive eating), and explores what she calls "the healthy trinity"--digestion, balance, and whole foods. Adler guides and encourages readers to shift their diet to achieve this desirable balance, introduces power foods we should all eat, and provides healthy ways to lose weight, along with simple recipes to optimize health. With her personal story interwoven, readers will be inspired to embrace the healthy power of food"--